2014
DOI: 10.2149/tmh.2013-26
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Medical Interventions for the Elimination of Preventable Blindness

Abstract: Background: Health authorities are working toward the global elimination of trachoma by the year 2020 with actions focused on the World Health Organization SAFE strategy (surgery of trichiasis, antibiotics, face washing and environmental changes) with emphasis on hygienist approaches for education.Objectives: The present survey was performed to assess the sustainability of the SAFE strategy 3 years after trachoma was eliminated from 6 villages.Methods: In February 2013 a rapid trachoma assessment was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…An analysis on the risk factors for trachoma provides important information for planning and implementing actions in disease control programs [5,14,15,23]. The present study revealed factors that were associated with occurrences of the disease, using households as the database.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…An analysis on the risk factors for trachoma provides important information for planning and implementing actions in disease control programs [5,14,15,23]. The present study revealed factors that were associated with occurrences of the disease, using households as the database.…”
Section: Discussionmentioning
confidence: 79%
“…To reach the global elimination of trachoma as a cause of blindness by 2020, WHO established a goal of carrying out population-based surveys among samples to verify the epidemiological situation [7,11,12] and implementing the SAFE strategy to control trachoma (S-surgery in cases of trachomatous trichiasis; A-antibiotic therapy in cases of active trachoma; F-facial hygiene; and E-environmental improvements) [13]. Use of the SAFE strategy has been shown to be a tool for reducing the prevalence of active forms of the disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…As largely reported, the antibiotic (azithromycin) administered to treat trachoma is bioavailable and highly active against the intracellular microorganisms triggering trachoma ( Chlamydiae ) [ 41 , 42 ]. This antibiotic eradicates Chlamydia from the conjunctival cells in a few weeks and dramatically reduces the clinical signs of active trachoma (follicles in the conjunctiva) [ 8 , 9 , 43 ]. Moreover, azithromycin treatments revealed no evidence that Chlamydiae lost their susceptibility to this antibiotic by post-transcriptional methylation of the 23S bacterial ribosomal-RNA, either plasmid or chromosome-mediated [ 44 , 45 ].…”
Section: Limitations Of Medical Interventions For the Elimination Of mentioning
confidence: 99%
“…In fact, 14 trials that included 3,587 participants and 15 trials that included 8,678 did not allow highlighting of the real impact of antibiotic treatment on the long-term elimination of clinical active trachoma, showing first, that clinical signs of trachoma re-emerged in treated communities, and second, that Chlamydia genomes were detected in conjunctival samples after repeated implementation of the four components of the SAFE strategy. The evidence at this point suggests that trachoma was partially reduced but not eliminated by repeatedly implementing the WHO strategy [ 43 , 47 49 ]. These facts suggest that the microbiological episteme makes it unreasonable to justify the repeated administration of active antibiotics in the same district to the same people (5, 7, 9 times or even more) to treat susceptible germs, and therefore that further analysis cannot be restricted to mathematical predictors, laboratory results or the opinions of eye-surface specialists [ 11 , 43 , 49 , 50 ].…”
Section: Limitations Of Medical Interventions For the Elimination Of mentioning
confidence: 99%
See 1 more Smart Citation